A metamorfose de uma janela : convergência entre a fotogenia e a aura na imagem em movimento - Silva, Mafalda Marisa Relvas da, 1990- (2015)
In a moment the window is transformed before the observant eye of the spectator. That fleeting moment allows the window to transfigure into something that is not architecture or painting, but something that overcomes the object itself and heightens it’s own duplicity. It becomes an object to see and to be seen. It is in this ambiguity, between framing and being an image per se, that glance is drawn to the object. The study focuses on the window’s moving image in a search to determine how can one perceive the visual metamorphism, through the convergence of two concepts, the photogenie and the aura. Other audiovisual notions are investigated like the enframing, the frame, the movement, the duration and the image desfamiliarization. The window is seen as a character revealed during a specific time by motion and light, throughout mediation